A PROSPECTIVE STUDY OF DRUG UTILIZATION AND QUALITY OF LIFE IN PSORIASIS PATIENTS IN DERMATOLOGY DEPARTMENT OF A TERTIARY CARE TEACHING HOSPITAL - Patel, Dhara; Pillai, Ajita; Nariya, Sweta; Bhuptani, Neela (Journal of Biomedical and Pharmaceutical Research, 2021)
Purpose/aim: To assess the current prescription pattern, efficacy, tolerability and impact on Quality of life(QoL) in psoriasis patients.Material: An observational, prospective study of 18 months was carried out in a tertiary care teaching hospital. Newly diagnosed patients of psoriasis, aged ≥ 18 years were included in the study. The demographic, clinical profile, psoriasis area severity index (PASI) and drug utilization were recorded. Follow up was done at 15 days interval for two and a half months. Patient’s QoL was assessed using Psoriasis Disability Index (PDI).Results: A total 100 patients were enrolled in the study. At the time of diagnosis, 43 patients had PASI score ≤10 and 57 had > 10. At the last follow up 96 patients had PASI sore ≤ 10 and 4 had > 10. Mean of QoL at the time of diagnosis was 10.43 and at the last follow up 6.1. Pre and post-treatment PASI score showed direct intermediate significant correlation with pre and post-treatment QoL score. Most frequently fixed drug combination(FDC)of steroid and keratolytic agent were prescribed followed by anti-histaminics, steroids, minerals, anti-microbial agents, emollients, vitamins, H2-blockers, immunosuppressants, and NSAIDS.WHO core indicators were used to analyse drugs prescribed.Conclusions: In this study, the treatment of psoriasis is according to the “NICE” guideline. Patient’s treatment adherence increased because of the QoL improvement. Thus, the QoL tools are important measure of patient satisfaction and treatment monitoring.Keywords: Psoriasis area severity index, Psoriasis Disability Index, Quality of life, Drug Utilization in Psoriasis